2018
DOI: 10.1002/hed.25368
|View full text |Cite
|
Sign up to set email alerts
|

Detection of circulating HPV16 DNA as a biomarker in the blood of patients with human papillomavirus‐positive oropharyngeal squamous cell carcinoma

Abstract: Background Development of biomarker analysis using the circulating cell‐free DNA (cfDNA) methodology is a challenge for noninvasive cancer diagnosis. In this study, a comparison between the plasma and tumor tissue HPV16 DNA viral loads (VLs) has been presented. Methods Real‐time polymerase chain reaction was performed for quantitating of HPV16 DNA in the plasma and tumor samples of patients with oropharyngeal cancer. Results Among the tissues, HPV16‐positive patients with oropharyngeal squamous cell carcinoma,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 41 publications
2
20
0
5
Order By: Relevance
“…These results are in contrast to our findings in which HPV16 VL was higher in nonsmokers than that in smokers. We also previously found that HPV16 VL was higher in nonsmokers in HPV-dependent oropharyngeal cancer [18].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…These results are in contrast to our findings in which HPV16 VL was higher in nonsmokers than that in smokers. We also previously found that HPV16 VL was higher in nonsmokers in HPV-dependent oropharyngeal cancer [18].…”
Section: Discussionsupporting
confidence: 56%
“…The level of HPV16 VL observed by us in the anal cancer tissues (median 2.12; l.q 1,17 -u.q. [18]. The HPV VL of other types was slightly lower than the HPV16 VL, though, without statistical significance.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In other words, EBV DNA in patients with NPC has a tendency to be specific for men with N2/N3 disease who never smoked. Interestingly, a similar tendency was also observed in HPV‐positive patients oropharyngeal cancer in our previous study . We showed that in patients with oropharyngeal cancers, no smoking and advanced N disease were the most important predictors for circulating HPV16 DNA in the blood.…”
Section: Discussionsupporting
confidence: 87%
“…Plasma circulating tumour HPV DNA (ctHPVDNA) is a promising biomarker for monitoring treatment responses in patients with HPV-associated OPC [15]. According to the results, the patients with ctHPVDNA OPC possessed significantly higher HPV DNA viral loads in their tumour tissues than the ctHPVDNA-negative patients [16]. Longitudinal monitoring of ctHPVDNA during post-treatment surveillance could accurately detect clinical disease recurrence [17].…”
Section: Discussionmentioning
confidence: 99%